Strategi Kepala Madrasah untuk Meningkatkan Motivasi Kerja Guru - Shofirah, Nurul Hafshotus; Noviawati , Khofifah Tri; Firmansyah, Joni; Mu’alimin (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
The goal of the madrasah principal's approach is to enhance the effectiveness of teachers during the teaching-learning process. For the best possible educational quality to be achieved, teachers must have a high level of job motivation. Data was gathered qualitatively through the literature observation method, which involves analyzing a range of pertinent literature sources. The study's findings indicate that a number of practical tactics, such as praising colleagues for their accomplishments, cultivating positive working relationships, efficient communication, establishing a happy workplace, and allocating suitable duties and responsibilities. The research's conclusions highlight the critical role that management plays in establishing the culture of the workplace, as well as the significance of honoring motivational elements and creating strategies for human resource development. This study offers a significant theoretical and practical contribution to our understanding of successful strategies for raising employee motivation at work in order to meet organizational objectives.